REGULASI DIRI OTONOM DAN TERKONTROL PADA PASIEN DIABETES MELLITUS TIPE 2 - Maghfirah, Sholihatul; Rohmadi, Rohmadi (Universitas Muhammadiyah Jember, 2016)
Diabetes Mellitus (DM) is a chronic disease with a high incidence in Indonesia and a serious health problem in Indonesia. DM management must to do a lifetime, and it make patients not adherent and become desperate. Uncontrolled diabetes can cause complications such as blindness, kidney failure, heart failure, and stroke. Disobedience and desperation patients in treatment may be due to low selfregulation. The level of self-regulation affects the behaviors, which in this case is the management of DM. The purpose of this study is to explain about autonomous selfregulation and controlled self regulation in patients with type 2 diabetes mellitus.The study design was descriptive. Total sample of 40 people. The research location was in Prolanis dr. Yunita and Prolanis dr. Ani Ruliana. The research instrument used a modification of Treatment Self-Regulation Questionnaire (TSRQ) for Diabetes. The results showed that 34 (85%) had a high autonomous self-regulation and 24 people (60%) had a low controlled self-regulation. Advice for health workers to give support and motivation to clients with diabetes to improve controlled self-regulation.